Stress Kerja dan Konflik Kerja Mempengaruhi Kinerja Perawat - Muhammad Amin; Yogi Ekwinaldo; Yesi Novrianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the relationship between work stress and work conflict on nurses' performance in the inpatient ward of the Kepahiang Regional General Hospital. This type of research is descriptive-analytic research with a cross-sectional approach. Statistical test results from 80 respondents: as many as 39 respondents (48.8%) have low work stress, and 41 (52.1%) respondents have high work stress. as many as 43 respondents (53.8%) stated there was no conflict, and 37 (46.2%) respondents stated that there was a conflict, the results of continuity correction for work stress (P) = 0,000 <α = 0.05 and continuity work conflict correction (P) = 0.000 <α = 0.05. In conclusion, there is a significant influence between work stress and work conflict on the performance of nurses in the inpatient room of the Kepahiang Regional General Hospital. Keywords: Nurse Performance, Work Conflict, Work Stress